International Accounting and Finance Handbook, Second Edition (Book). - Williams, Thomas H.; Eichenseher, John W. (The Accounting Review, 1998)
Reviews the book "International Accounting and Finance Handbook," 2nd ed., edited by Frederick D.S. Choi.